Inhibition of myocardial cathepsin-L release during reperfusion following myocardial infarction improves cardiac function and reduces infarct size. Issue 6 (16th June 2021) - He, Weihong; McCarroll, Charlotte S; Nather, Katrin; Ford, Kristopher; Mangion, Kenneth; Riddell, Alexandra; O'Toole, Dylan; Zaeri, Ali; Corcoran, David; Carrick, David; Lee, Mathew M Y; McEntegart, Margaret; et al.
Abstract: Aims: Identifying novel mediators of lethal myocardial reperfusion injury that can be targeted during primary percutaneous coronary intervention (PPCI) is key to limiting the progression of patients with ST-elevation myocardial infarction (STEMI) to heart failure. Here, we show through parallel clinical and integrative preclinical studies the significance of the protease cathepsin-L on cardiac function during reperfusion injury. Methods and results: We found that direct cardiac release of cathepsin-L in STEMI patients ( n = 76) immediately post-PPCI leads to elevated serum cathepsin-L levels and that serum levels of cathepsin-L in the first 24 h post-reperfusion are associated with reduced cardiac contractile function and increased infarct size. Preclinical studies demonstrate that inhibition of cathepsin-L release following reperfusion injury with CAA0225 reduces infarct size and improves cardiac contractile function by limiting abnormal cardiomyocyte calcium handling and apoptosis. Conclusion: Our findings suggest that cathepsin-L is a novel therapeutic target that could be exploited clinically to counteract the deleterious effects of acute reperfusion injury after an acute STEMI.